Copper(II)‐Specific Fluorogenic Task‐Specific Ionic Liquids as Selective Fluorescence Probes and Recyclable Extractants. Issue 40 (18th August 2015) - Chatterjee, Sobhan; Gohil, Hardipsinh; Suresh, E.; Paital, Alok Ranjan
Abstract: The designed synthesis of a series of copper(II) specific fluorogenic hydrophobic task‐specific ionic liquids (TSILs) from a new naphthalene‐based tetradentate ligand is reported. Absorption and fluorescence spectral studies reveal both the ligand and its derivative TSILs show exclusive selectivity towards copper(II) ions. The Stern–Volmer method for calculation of the detection limit for ligand andTSIL1–3 shows values of 0.12, 20, 17, and 15 μM, respectively. Extraction and striping studies by doping these TSILs in [bmim][NTf2 ] demonstrated that these TSILs are recyclable extractants for the selective recovery of Cu II ions from a mixture of 14 relevant metal chloride aqueous solutions in biphasic liquid–liquid extraction with approximately 95 % recovery. Abstract : Two for one! A series of fluorogenic hydrophobic task‐specific ionic liquids, (TSIL) derived from a naphthalene‐based tetradentate ligand act as selective fluorescent probes (see figure, X=Y=Cl or X=Cl, Y=NTf2 ) and recyclable extractants for selective separation of Cu II ions from aqueous solutions in biphasic liquid–liquid extraction.